War and the American difference : theological reflections on violence and national identity - Hauerwas, Stanley, 1940- (Grand Rapids, Mich. : Baker Academic, 2011)
How are American identity and America's presence in the world shaped by war, and what does God have to do with it? Esteemed theologian Stanley Hauerwas helps readers reflect theologically on war, church, justice, and nonviolence in this compelling volume, exploring issues such as how America depends on war for its identity, how war affects the soul of a nation, the sacrifices that war entails, and why war is considered "necessary," especially in America. He also examines the views of nonviolence held by Martin Luther King Jr. and C. S. Lewis, how Jesus constitutes the justice of God, and the relationship between congregational ministry and Christian formation in America.
War and the American difference: a theological assessment -- America's God -- Why war is a moral necessity for America, or, How realistic is realism? -- Reflections on the "appeal to abolish war", or, What being a friend of Enda's got me into -- Sacrificing the sacrifices of war -- C.S. Lewis and violence -- Martin Luther King, Jr. and Christian nonviolence -- Jesus, the justice of God -- Pentecost: learning the languages of peace -- A worldly church: politics, theology, and the common good -- A particular place: the future of parish ministry -- Beyond the boundaries: the church is mission.
Includes bibliographical references and index.
Keywords: War -- Religious aspects -- Christianity; Nonviolence -- Religious aspects -- Christianity; Nationalism -- Religious aspects -- Christianity; Christianity and international relations; Christianity and politics -- United States; Church and state -- United States; United States -- Foreign relations -- 2001-